2016
DOI: 10.1292/jvms.16-0293
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastrointestinal helminth parasites of zoonotic significance in dogs and cats in lower Northern Thailand

Abstract: Gastrointestinal zoonotic helminths of dogs and cats have a public health concern worldwide. We investigated the prevalence of gastrointestinal helminths of zoonotic significance in dogs and cats in lower Northern Thailand and utilized molecular tools for species identification of hookworms and Opisthorchis viverrini. Fecal samples of 197 dogs and 180 cats were collected. Overall prevalence of infection using microscopy was 40.1% in dogs and 33.9% in cats. Helminth infection found in both dogs and cats include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
4
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 35 publications
3
38
4
5
Order By: Relevance
“…Strongyloides infection rate in dogs was reported to be as low as 0.4% in Okinawa, Japan [31]. Although we can’t find any reports about Myanmar canine strongyloidiasis, infection rate in Myanmar is possibly very high as reported in other Southeast Asian countries [32,33]. Therefore, a genome-wide investigation of their population structures would be of interest to see if a similar intra-genome heterozygosity trend can be observed as in human Strongyloides and to identify if there are interspecies transmissions between dogs and humans.…”
Section: Discussionmentioning
confidence: 87%
“…Strongyloides infection rate in dogs was reported to be as low as 0.4% in Okinawa, Japan [31]. Although we can’t find any reports about Myanmar canine strongyloidiasis, infection rate in Myanmar is possibly very high as reported in other Southeast Asian countries [32,33]. Therefore, a genome-wide investigation of their population structures would be of interest to see if a similar intra-genome heterozygosity trend can be observed as in human Strongyloides and to identify if there are interspecies transmissions between dogs and humans.…”
Section: Discussionmentioning
confidence: 87%
“…The high proportion of Ancylostoma-infected dogs in these tropical climates is exacerbated by the co-existence of several risk factors that allow the parasite to thrive in dogs and significantly increase their risk of infecting humans i.e. free ranging community dogs, a lack of veterinary care, irregular deworming, roaming behaviour and poor environmental hygiene [35,[37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…In Thailand, previous reports revealed that Toxocara eggs were found in the stool of dogs and cats [24,25]. Furthermore, Toxocara eggs were identified in raw vegetables from markets in southern Thailand [26]; however, their impact on humans has not been investigated.…”
Section: Introductionmentioning
confidence: 99%